Polymorphism Study of 1,2,4-Triazole Derivatives: Impact on Drug Efficacy and Stability - Shirish Inamdar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Polymorphism, the phenomenon where a substance exists in multiple crystalline forms, is pivotal in the pharmaceutical industry. This study explores the polymorphism of 1,2,4-triazole derivatives and its influence on drug efficacy and stability. Using a variety of analytical techniques, we characterized the polymorphic forms of selected triazole derivatives and assessed their biological activities and stability under various conditions. 1,2,4-Triazole derivatives, known for their antifungal, antibacterial, anticancer, and antiviral activities, can exhibit multiple polymorphic forms, which can substantially affect their physical, chemical, and biological properties, thereby influencing drug efficacy and stability. We selected several derivatives based on their pharmacological relevance and available polymorphic forms. Characterization was performed using X-ray crystallography for crystal structure determination, differential scanning calorimetry (DSC) for analyzing thermal properties and phase transitions, and powder X-ray diffraction (PXRD) for identifying and differentiating polymorphic forms through diffraction patterns. Drug efficacy was evaluated through in vitro assays and in vivo studies that examined biological activity and pharmacokinetic properties in animal models. X-ray crystallography revealed distinct molecular arrangements and intermolecular interactions among polymorphs. DSC analysis showed variations in melting points and thermal behaviors, while PXRD identified multiple polymorphic forms with unique diffraction peaks. In vitro assays indicated differing levels of biological activity among polymorphs, with some exhibiting enhanced efficacy, and in vivo studies revealed varying pharmacokinetic profiles affecting therapeutic outcomes. This research underscores the significant impact of polymorphism on the efficacy and stability of 1,2,4-triazole derivatives, emphasizing the importance of understanding polymorphism for optimizing drug development and ensuring consistent therapeutic performance. Future research should focus on controlling polymorphic forms during synthesis and formulation to improve drug efficacy and stability.